The Two Worlds of Marcel Proust - March, Harold (University of Pennsylvania Press, 2016)
There have been many specialized studies of Proust, and his character and viewpoint have been violently attacked and warmly defended. Here at last, written with sound scholarship but addressed to the general reader, is a full, frank, and unbiased account of the man and his work--and a clear statement of what he has to say to the world today.